An examination between census tract unhealthy food availability and colorectal cancer incidence. (August 2020) - Gibson, Derrick C.; Prochaska, John D.; Yu, Xiaoying; Kaul, Sapna
Highlights: Unhealthy food availability was weakly associated with colorectal cancer incidence Higher rates of poverty were associated with higher colorectal cancer incidence Research should examine how the built environment influences colorectal cancer risk Abstract: Background: Unhealthy food environments may be associated with higher risks of developing diet-related cancers, such as, colorectal cancer. We conducted an ecological analysis to evaluate the relationship between the local food environment and colorectal cancer incidence overall and separately for males and females. Methods: Data from the Texas Cancer Registry was utilized to geocode individuals aged 40 years and older diagnosed with colorectal cancer from 2005 to 2015 to their residential 2010 census tract. Total number of establishments classified as Limited Service Restaurants for each census tract was retrieved from the 2005 Business Patterns Survey by using a crosswalk to map zip codes to census tract. Census tract unhealthy food availability was calculated by dividing the estimated number of Limited Service Restaurant establishments in each census tract by the census tract population and divided into quartiles. Generalized estimating equations were used to assess the association between unhealthy food availability quartiles and colorectal cancer incidence. Results: Adjusting for the census tract level sociodemographic characteristics, the incidence of colorectal cancer was slightly higher in unhealthy food availability quartile 2 (Incidence Rate Ratio (IRR) = 1.03, 95 % CI: 1.00–1.05), but not quartile 3 (IRR = 1.02, 95 % CI: 1.00–1.05), and quartile 4 (highest availability, IRR = 1.02, 95 % CI: 0.99–1.05) compared to census tracts with lowest unhealthy food availability. Conclusion: Colorectal cancer incidence was not strongly associated with census tracts with higher unhealthy food availability. Future observational studies should be conducted to examine the influence of the built environment on colorectal cancer risk.